Two-gradient direction FXLMS: An adaptive active noise control algorithm with output constraint. (1st February 2019) - Shi, DongYuan; Gan, Woon-Seng; Lam, Bhan; Shi, Chuang
Highlights: Active noise control algorithm with output constraint. It has the same computational complexity as the conventional FXLMS, while maintaining a stricter output constraint that minimizes the saturation distortion. Algorithm based on the Hemstitching method, which prevents the output saturation of the actuator. Abstract: Active noise control (ANC) is broadly used to cancel the unwanted disturbance in different fields because of its excellent performance in abating low-frequency noise. In practice, however, the limited driving capability of actuators restrict the maximum output power of ANC systems. Once the driving signal of the ANC system exceeds these limitations, the inherent nonlinearity of the actuators will deteriorate the noise reduction and may result in the divergence of the adaptive algorithm. Hence, the two-gradient direction filtered-x least mean square (2GD-FXLMS) algorithm based on the optimal Kuhn-Tucker solution with the output constraint is proposed in this paper. This algorithm has the advantage of minimizing system overdriving, maintaining a specified power budget, and enhancing system stability. Compared to existing output-constrained adaptive algorithms, this proposed algorithm has the same computational complexity as the conventional FXLMS algorithm, while maintaining a stricter output constraint that minimizes the saturation distortion.